Peningkatan Literasi Digital Mahasiswa Kesehatan melalui Workshop Artificial Intelligence dalam Transformasi Kesehatan Digital - Siswati, Sri; Syafrawati; Amelia, Silvi; Khairunnisa, Muthia (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Digital transformation in the health sector has accelerated the adoption of Artificial Intelligence (AI) in academic and professional environments. However, concerns regarding ethical implications, academic integrity, and digital health literacy persist among health sciences students. This study aimed to assess the baseline levels of AI utilization, perceived usefulness, and ethical awareness among students in a public health faculty, as the foundation for implementing a capacity-building workshop on responsible AI use. A descriptive cross-sectional survey was conducted involving 181 undergraduate and postgraduate students from the Faculty of Public Health, Universitas Andalas, who completed a structured online questionnaire prior to the workshop. Data were analyzed descriptively using frequency distributions and percentages to identify patterns of AI usage and ethical concerns. Results showed that 94.5% of respondents actively used generative AI tools, primarily for academic tasks such as searching for scientific references and completing assignments. Despite high adoption, 44.2% reported moderate concerns related to plagiarism, algorithmic bias, and data privacy. Students predominantly obtained AI-related knowledge from social media platforms rather than formal learning sources. These findings indicate a substantial digital utilization gap, particularly in ethical and critical literacy dimensions, highlighting the need for structured educational interventions. Integrating AI literacy, emphasizing ethical responsibility and critical evaluation into the curriculum of health sciences education is recommended to prepare future health professionals for equitable and trustworthy digital health transformation.